IDENTIFICATION OF LIVER STRUCTURE AND MORPHOMETRY OF BALI DUCKS AT DIFFERENT AGES - Lase, Linus Putra Jaya; Suatha, I Ketut; Heryani, Luh Gde Sri Surya; Susari, Ni Nyoman Werdi; Setiasih, Luh Eka (Buletin Veteriner Udayana, 2023)
The liver is an important organ in the body that performs many important functions in the digestive system. This study aims to determine the structure and liver morphometry of Bali ducks at different ages. The anatomical structures observed in this study were the number of lobes, color and morphometry (weight, length, width, and volume) of the liver. This study used 18 male bali ducks aged 1 month, 3 months, and 5 months. The ducks were necropsied and the liver was taken, then anatomical observations and morphometric measurements were carried out. The results showed that there were no differences in the anatomical structure at different ages. Based on anatomical measurements, there are differences in liver morphometry of Balinese ducks at different ages which are marked by differences in liver weight, length, width and volume. It is necessary to do further research on histomorphometric measurements at different ages.